Angels and demons in political brawl in the face of Latin American Indigenous Constitutionalism - Narváez, Iván (2021)
This article outlines the substantive content of Latin American Indigenous Constitutionalism; as a locution of millenary cognitive practices, social mobilizations and emancipatory uprisings that validate the collective epistemological construction of the managerial sense of the State, society, and life: this is their standard of recognition. One goal is to connote how this Constitutionalism radiates a political approach that unhinges the legionaries of nineteenth century, of transnational constitutional theory and the “Lex Mercatoria”; And, in the other side, reveal the ineffectiveness of the so-called New Constitutionalism implemented under the guidelines of the Report of the Trilateral Commission of 1975. Three key conditions of the Latin American socio-economic political crisis of the 1960´s and 1970´s are described as backgrounds, and decisive for the establishment of military dictatorships that, after taming society, they organize the return to electoral democracy and the adoption of that New Constitutionalism. The descriptive-analytical perspective assumed, allows to make visible the ontological change that contributes to the reposting of the ´other knowledge´, of the ´other powers´ in the scenario of the current political conflict, as well as its impact on the construction of a new hegemony due to the power dispute. The watchword is that without power there is no change.